2009
DOI: 10.1271/bbb.80860
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Branched Units at Position 6 in the Reactivity of a Unique Variety of β-D-Glucan fromAureobasidium pullulansto Antibodies in Human Sera

Abstract: We recently determined the structure of a unique type of 1,3--D-glucan obtained from Aureobasidium pullulans (AP-FBG) and found that it reacted with the antibodies in human sera. The reactivity of AP-FBG to the antibodies was stronger than that of 1,3--D-glucan obtained Grifola frondosa (GRN) but weaker than that of 1,3--D-glucan from Candida albicans (CSBG). Here, we demonstrated that AP-FBG reacted to IgG antibodies, especially those of the subclasses IgG2, IgG1, and IgG3, in human sera. Moreover, the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…(9,10) We also revealed that AP-FBG could induce the production of cytokines in a splenocyte culture system derived from DBA/2 mice, which are highly sensitive to β-d-glucan. (11)(12)(13)(14)(15) However, the mechanism(s) by which AP-FBG, which possesses a characteristic high 6-branching structural feature, induced the production of cytokines by immune cells has not been determined.…”
Section: Research Articlementioning
confidence: 80%
“…(9,10) We also revealed that AP-FBG could induce the production of cytokines in a splenocyte culture system derived from DBA/2 mice, which are highly sensitive to β-d-glucan. (11)(12)(13)(14)(15) However, the mechanism(s) by which AP-FBG, which possesses a characteristic high 6-branching structural feature, induced the production of cytokines by immune cells has not been determined.…”
Section: Research Articlementioning
confidence: 80%
“…A. pullulans is well known for its production of pullulan, a neutral polysaccharide of repeating maltotriose units, which has numerous applications in medicine, pharmacy, the food industry, and other fields [2, 3]. A. pullulans also produces a β-glucan that shows high reactivity to human IgG antibodies [4] and possible beneficial immunomodulatory effects [5]. A. pullulans has an unusually large spectrum of extracellular enzymatic activities [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…The β-(1,3)-glucans are well-known pro-inflammatory agents [13,14] and innate immune responses can be induced through binding to monocytes or macrophages via the receptor dectin-1 [15] or complement receptor 3 (CR3) [16]. Adaptive immune responses to β-glucan have received much less attention, but anti-β-(1,3)-glucan antibodies have previously been reported [17,18] and their measurement has been suggested useful for the diagnosis of candidiasis [19]. Recently Chiani et al [20] reported high anti-β-glucan IgG levels in human sera, in a study on the use of β-glucans in vaccines.…”
Section: Introductionmentioning
confidence: 99%